Students' Interest in Differentiated Learning on Manipulative Movement Material Throwing and Catching a Soaring Ball at Class 2 of Wonojoyo 2 Elementary School - Sulthon, Mochamad; Abdau, Aqil; Suryani, Dwi Maulita Yuli; Laksono, Danur Satyo; Yusuf, Emha Faisal; Puspodari (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
This study aims to analyze the interest of students in differentiated learning on manipulative motion material toss catch the ball bounce in Grade 2 SD Negeri Wonojoyo 2. Differentiated learning is designed to meet the needs of students who are diverse in learning abilities and styles. The research method used is descriptive quantitative approach with data collection through observation, interviews, and questionnaires. The results showed that differentiated learning was able to increase students ' interest in manipulative motion materials. This is shown through increased student active participation, enthusiasm during learning, and the level of student understanding of the material taught. This study contributes to the development of more inclusive and effective learning methods in primary schools.